Analisis Kinerja Simpang Empat Tak Bersinyal Pada Ruas Jalan Cempaka – Jalan Teratai Pekanbaru - Aidi Yani Fitri; Sri Djuniati; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Crossroad is an intersection of two or more roads that joins or crosses each other and often run into traffic conflicts. The intersection of Cempaka Road – Teratai Road is one of a intersection without traffic signs. Traffic conflicts, such as traffic jams during the peak hour, have happened frequently in this intersection. This study’s objective is to calculate the performance of this intersection based on Indonesian Highway Capacity Manual (Manual Kapasitas Jalan Indonesia, MKJI) 1997. The study took three days to finish; Saturday (28/10/2017), Sunday (29/10/2017), until Monday (30/10/2017), with observation hours happening during morning (07.00-09.00 WIB), noon (11.00-14.00 WIB) and afternoon (16.00-19.00 WIB). Based on the conducted surveys and traffic calculation, traffic peak hours happen on Monday from 16.45 to 17.45 WIB with the value of Q = 2984,5 smp/hr, C = 3170 smp/hr, Ds = 0,94, DTI = 12,70 s/smp, DTMA = 9,08 s/smp, DTMI = 19,91 s/smp, DG = 4,02 s/smp, D = 16,72 s/smp, and QP = 36 - 70%.. Due to the calculated Ds having a value higher than the value stated by MKJI which is 0,75, a planning and regulation needs to be done for the intersection of Cempaka Road – Teratai Road. In order to make the value of Ds for this intersection lower than 0,75, a lane (B) prohibiton and a widening of the major lanes from 7,7 m and 7,6 m into 9,7 m and 9,6 m respectively were done and then the Ds value for Cempaka Road – Teratai Road intersection finally reaches the intended target with the value being 0,69.Keywords: Intersection without traffic sings, traffic flow, capasity, degree of saturation